Mechanisms underlying the cardioprotective effect of Salvianic acid A against isoproterenol-induced myocardial ischemia injury in rats: Possible involvement of L-type calcium channels and myocardial contractility. (2nd August 2016) - Song, Qiongtao; Chu, Xi; Zhang, Xuan; Bao, Yifan; Zhang, Yuanyuan; Guo, Hui; Liu, Yang; Liu, Hongying; Zhang, Jianping; Zhang, Ying; Chu, Li
Abstract: Ethnopharmacological relevance: Salvianic acid A (SAA), which is the main water-soluble fraction in Radix Salviae Milthiorrhizae, has been widely applied for treating cardiovascular diseases in China. Aim of the study: To explore the effects of SAA against myocardial ischemia injury induced by isoproterenol (ISO) in rats and to clarify its underlying myocardial protective mechanisms based on l -type calcium channels and myocardial contractility. Materials and methods: The myocardial ischemia injured rat model was induced by administering ISO (85 mg/kg) subcutaneously at evenly spaced intervals throughout the day and night for 2 consecutive days. Serum cardiac biomarkers were analyzed, and heart tissues were isolated and prepared for histopathology assay. The regulatory effects of SAA on the L-type calcium current (ICa-L ) in rat ventricular myocytes were observed by the patch clamp technique. The IonOptix Myocam detection system was used to observe the contractility of isolated rat ventricular myocytes. Results: SAA significantly ameliorated changes in heart morphology and electrocardiographic patterns and reduced serum levels of creatine kinase and lactate dehydrogenase in the ISO-induced myocardial ischemia injured rat model. Meanwhile, SAA reduced ICa-L in a concentration-time dependent way with an IC50 of 1.47×10 −5  M, upshifted the current-voltage, activation, and inactivation curves of ICa-L, and significantly inhibited the amplitude of the cell shortening. Conclusions: These results indicate that SAA exhibits significant cardioprotective effects against the ISO-induced myocardial ischemia injury, potentially through inhibiting ICa-L and decreasing myocardial contractility. Graphical abstract: